Pengaruh Struktur Aset Dan Pertumbuhan Aset Terhadap Struktur Modal - Apriliah , Dika; Pratiwi, Aliah; Huda, Nurul (Cattleya Darmaya Fortuna, 2024)
This research was conducted with the aim of examminingthe influence of Asset Structure, Asset Growth on Capital Structure at PT. Indofarma Tbk is listed on the indonesia Stock Exchange (BEI) for the period 2001-2022 .The use of data in this research is based on quantitative data. The reseach instrument used to measure this research uses data on total assets, fixed assets, debt and capital from the balance sheet financial report at PT. Indofarma Tbk. The population of this research is the financial statements of PT. Indofarma Tbk for 21 years, namely from 2001-2022. The sample in this research is the financial report of PT. Indofarma Tbk for 12 years, namely 2001-2022. The sampling technique used in this research was purposive sampling. The data collection teachnique used in this research are documentation and literature study.The data analysis technique in this research is using the classic assumption test, multiple linear regression test, t test, f test using the SPSS 24 program. The research results show that the Asset Struktur variable partially influences Capital Structure,while the Asset Growth variable partially infuences Capital Structure. Simultaneously, the Asset Structure and Asset Growth variables influence Capital Structure.